Jesus' Use of Experiential Learning in the Sending of the Seventy: Implications for Ministry Practicums. Issue 1 (April 2021) - Nehrbass, Kenneth; Rhoades, Jane
Among His many teaching techniques, Jesus used experiential learning to link the disciples' previous knowledge with real-world experiences. This article explores Jesus' teaching techniques in the sending of the seventy(two) into Samaritan territory (Lk. 10:1-17). We discuss Jesus' andragogical methods in light of current experiential learning theories, especially the Joplin-Linhart model. Last, we describe how church leaders could leverage the lessons from Jesus' use of "practicums" to help Christians reflect on their own ministry experiences.